Ecdysone regulates Drosophila wing disc size via a TORC1 dependent mechanism - Straßburger, Katrin; Lutz, Marilena; Müller, Sandra; Teleman, Aurelio A. (Nature Communications, 2021)
Most cells in a developing organ stop proliferating when the organ reaches a correct, final size. The underlying molecular mechanisms are not understood. We find that in Drosophila the hormone ecdysone controls wing disc size. To study how ecdysone affects wing size, we inhibit endogenous ecdysone synthesis and feed larvae exogenous ecdysone in a dose-controlled manner. For any given ecdysone dose, discs stop proliferating at a particular size, with higher doses enabling discs to reach larger sizes. Termination of proliferation coincides with a drop in TORC1, but not Dpp or Yki signaling. Reactivating TORC1 bypasses the termination of proliferation, indicating that TORC1 is a main downstream effector causing proliferation termination at the maximal ecdysone-dependent size. Experimental manipulation of Dpp or Yki signaling can bypass proliferation termination in hinge and notum regions, but not the pouch, suggesting that the mechanisms regulating proliferation termination may be distinct in different disc regions.